Efficacy Analysis of Cervical Cerclage in the Treatment of Cervical Insufficiencies - Qinghua Zhang; Yansong Liu; Changsheng Xu (IMR Press, 2023)
Background: This study aimed to assess the efficacy and safety of laparoscopic and transvaginal cervical cerclage treatments in patients with cervical insufficiency before and during pregnancy. Methods: A total of 70 patients diagnosed with cervical insufficiency and undergoing cervical cerclage at the Second Affiliated Hospital of Xinjiang Medical University between January 2020 and December 2022 were included. The patients were divided into three groups based on different surgical methods: transvaginal loop during pregnancy (Group 1, n = 30), transabdominal loop before pregnancy (Group 2, n = 20), and transabdominal loop during pregnancy (Group 3, n = 20). The groups were compared in terms of general clinical data, operation time, intraoperative bleeding, hospital stay, delivery gestational weeks, preterm delivery rate, prolonged gestational weeks, and neonatal births. Results: (1) There were no statistically significant differences in age, pregnancy, delivery, number of miscarriages, cervical length, and history of midterm pregnancy loss among the three groups (p > 0.05). (2) Prolonged gestational week, delivery gestational week, term delivery, and neonatal birth weight were higher in Groups 2 and 3 compared to Group 1, with statistically significant differences (p < 0.05). There was no statistically significant difference (p > 0.05) when comparing Group 2 and Group 3. Premature rupture of membranes and preterm delivery were higher in Group 1 compared to Groups 2 and 3, with statistically significant differences (p < 0.05). There was no statistically significant difference when comparing Group 2 and Group 3 (p > 0.05). (3) The amount of surgical bleeding and surgical time showed statistically significant differences (p < 0.05) among the three groups. Group 1 had more surgical bleeding than Groups 2 and 3, with statistically significant differences (p < 0.05). When comparing Group 2 and Group 3, Group 3 had more surgical bleeding than Group 2, with a statistically significant difference (p < 0.05). Group 2 had a shorter surgical time than Group 1 and Group 3, with statistically significant differences (p < 0.05). When comparing Group 1 and Group 3, Group 3 had a longer surgical time than Group 1, with a statistically significant difference (p < 0.05). There was no statistically significant difference in hospital stay when comparing three groups (p > 0.05). Conclusions: Laparoscopic cervical cerclage is a safe and effective treatment option, yielding better pregnancy outcomes than transvaginal cervical cerclage, particularly for patients with previous failed transvaginal cerclage. Preconception laparoscopic cervical cerclage carries lower surgical risks and should be considered for clinical application.